Right-Sided Subcutaneous Implantable Cardioverter Defibrillator System Implantation in a Patient with Complex Congenital Heart Disease and Dextrocardia: A Case Report and Literature Review - Bandar Al-Ghamdi (Case Reports in Cardiology)
Patients with complex congenital heart disease (CHD) and low left ventricular ejection fraction are at an increased risk of sudden cardiac death (SCD). Prevention of SCD by subcutaneous implantable cardioverter defibrillator (S-ICD) implantation may represent a valuable option in certain CHD patients. Patients with CHD and dextrocardia pose a challenge in S-ICD system implantation, and nonstandard device placement may be required. Furthermore, electrocardiogram (ECG) screening prior to S-ICD implantation in CHD patients has significant limitations. This case represents the placement of a S-ICD system on the right side of the chest in a 26-year-old male with severe biventricular failure and nonsustained ventricular tachycardia following multiple corrective surgeries of situs inversus totalis, double-outlet right ventricle with a ventricular septal defect, and pulmonary atresia. The use of S-ICDs in a CHD population and in particular CHD patients with dextrocardia and right-sided S-ICD implantation is briefly discussed.